The indications, complications and outcomes of dogs undergoing partial penile amputation: 10 cases (2014‐2021). (14th November 2022) - Ritson, K.; Bird, F.; Stefanidis, G.; Brissot, H.
Abstract : Objectives: To report the signalment, indications for surgery, postoperative complications and medium‐/long‐term outcomes in dogs undergoing partial penile amputation. Materials and Methods: Retrospective case series. The electronic medical records of a single small animal referral hospital were searched between January 2014 and January 2021 for dogs that underwent a partial penile amputation. Data collected included signalment, presenting clinical signs, indication for partial penile amputation, surgical technique, postoperative complications and outcome. Results: Ten dogs were included in the study. Indications for surgery were treatment of preputial neoplasia (n=5), penile neoplasia (n=1), idiopathic paraphimosis (n=3) and chronic urethritis (n=1). Five of five preputial tumours were cutaneous mast cell tumours, and the penile tumour was a squamous cell carcinoma. All dogs recovered uneventfully from surgery with a median postoperative hospitalisation time of 28.8 hours. Two of the three dogs treated for paraphimosis had major postoperative complications requiring further resection of the tip of the penis at 2 weeks and 24 months. Four dogs had minor complications managed without surgical intervention. The outcome was good to excellent in nine of nine dogs for which medium‐ or long‐term follow‐up data were available. Clinical Significance: In this group of dogs, partial penile amputation, performed with or without concurrent resection of the prepuce, was a well‐tolerated surgical procedure with low intraoperative and postoperative complication rates and good functional outcomes. Partial penile amputation should be considered for conditions affecting the distal penis and prepuce.